Feasibility of preparatory measures in the orthopedic treatment of TMJ dysfunction pain syndrome in patients with occlusion and articulation disorders - Proshchenko А. М. (Actual Dentistry, 2024)
Summary. Violations of any link of the dental-jaw system, for example, irrational reproduction of occlusion on the chewing surfaces during dental prosthetics, can disrupt its work, and as a result lead to symptomatic TMJ dysfunction, which may manifest as a headache, pain in the TMJ area with radiation in temple, occiput, neck, problems with the innervation of the facial area, and even disturbances in the work of the masticatory muscles. Purpose: to assess influencing factors and the need for preparatory measures in the orthopedic treatment of functional disorders of the masticatory apparatus caused by occlusal and articulatory disorders. Research materials and methods. Clinical and laboratory examination and orthopedic treatment of 150 patients with various variants of occlusal disorders were carried out, in 90 of them functional disorders of the masticatory apparatus were not accompanied by pain syndrome, in 60 patients TMJ dysfunction with pain syndrome. Research results. When assessing the state of the oral cavity, the following factors were identified that were associated with the need for preparation for orthopedic treatment: stable functional displacement of the LV (p = 0.00002), decrease in the interalveolar height (p = 1.60542E–08), unfixed bite (p = 4.06924E–11), the presence of maxillofacial deformities (p = 2.01E–11), supracontacts (p = 0.0016), dental row defects (p = 0.0008), crown teeth defects (p = 0.003), the presence of direct and indirect restorations with irrationally modeled occlusion on the chewing surfaces of the teeth (p = 0.002), pathological types of bite (p = 0.03). Conclusions. When planning orthopedic treatment for patients with occlusal-articulation disorders and TMJ dysfunction, 71.33% needed special preparatory measures. The choice of the preparatory measures or their combination depended on the clinical situation in the oral cavity and the choice of the occlusive therapy of TMJ dysfunction at the 1st stage of the orthopedic treatment complex. Keywords: orthopedic treatment, TMJ dysfunction, implantation, occlusion-articulation disorders.